Metode Pembelajaran Akidah Akhlak MI/SD - Susiba Susiba (el-Ibtidaiy:Journal of Primary Education, 2020)
This study uses the right method in learning Islamic MI/SD morals, because Islamic material gives a lot of things that are abstract, while new elementary children who can think concretely. This research was conducted to learn appropriate learning methods in learning MI/SD moral creed. The research method is a literature review, the source of data using primary and secondary data sources, and using data analysis techniques (content analysis). In this study found methods that are relevant to the learning of Islamic MI/SD A are: (1) Articulation Game Method, (2) Role playing method (3) Snowball throwing game (4) Lecture method (7) Question and Answer method (8) Mind Mapping Games (9) Sociodrama method (10) Demonstration method) (10) Method of analogizing something abstract into a concrete writing.